Skrining dan Edukasi pada Kelompok Rentan Tuberkulosis Paru (TB) Berbasis Teknologi Digital di Puskesmas Simpang Kawat Kota Jambi - Kurniawati, Eti; Merdekawati, Diah; Listiawaty, Renny; Yuniza, Yuniza; Syahirah, Riby Bintang (Universitas Malahayati Lampung, 2025)
ABSTRAK Tuberkulosis adalah suatu penyakit kronikmenular yang disebabkan oleh bakteri Mycobacteriumtuberculosis. Tahun 2020-2024 jumlah penderita TB di 20 Puskesmas mengalami peningkatan. Salah satu Puskesmas di Kota Jambi yangmemiliki banyak penderita TB adalah Puskesmas Simpang Kawat, dengan capaian suspek TB Paru sebanyak 541 (91,85 %) dengan prevalensi 1,9 sedangkan 62 pasien TB (+) yang mendapatkan layanan Kesehatan. Menjadi tugas penting bagi petugas kesehatan serta kader Posyandu dalam mencegah terjadinya peningkatan angka kejadian TB Paru. Tujuan pelaksanaan kegiatan yaitu adalah meningkatkan pengetahuan dan keterampilan mitra tentang SKrining pencegahan dan pengendalian TB Paru. Kegiatan diawali dengan FGD bersama Mitra kemudian dilanjutkan dengan pemberian materi tentang diabetes mellitus dan skrining ulkus diabetik serta pengenalan dan penggunaan tentang aplikasi SIFAR-TB. Metode pendekatan untuk mencapai target luaran adalah knowledge transfer dan technology transfer. Terdapat peningkatan pengetahuan dan keterampilan pada peserta tentang skrining TB Paru baik secara manual maupun dengan aplikasi SIFAR-TB. Kegiatan skrining dan edukasi pada kelompok keluarga rentan TB dapat dilakukan secara berkesinambungan agar penularan TB dapat dicegah sejak dini. Kata Kunci: Tuberkulosis, Skrining,Edukasi ABSTRACT Introduction: Tuberculosis is a chronic infectious disease caused by the bacteria Mycobacterium tuberculosis. In 2020-2024 the number of TB sufferers in 20 Community Health Centers increased. One of the Community Health Centers in Jambi City that has many TB sufferers is Simpang Kawat Community Health Center, with a reach of 541 (91.85%) suspected Pulmonary TB with a prevalence of 1.9 while 62 TB patients (+) who received health services. Partners have posyandu cadres for several health service activities in the community with a total of 35 people. Routine activities carried out by posyandu cadres are coordinated by partners such as cadres for infectious diseases and non-infectious diseases. The description of the sanitation conditions of the patient's house includes the physical condition of the house which is vulnerable to becoming a breeding ground for tuberculosis bacteria, thus causing an increase in the prevalence of Pulmonary TB. Objective: The purpose of implementing the activity is to increase the knowledge and skills of partners regarding early detection of TB prevention and control and to improve the quality of partner services for Pulmonary TB sufferers. Method: The approach method to achieve the output target is knowledge transfer and technology transfer. Output targets: increasing knowledge, skills and health services Results: This activity was carried out in August 2025, starting with the FGD of the Community Service Team with the Simpang Kawat Health Center Health workers, then mentoring and education for Health workers and Posyandu Cadres as well as screening activities for the TB-vulnerable community in the Simpang Kawat Health Center work area. Conclusion: Screening and education activities for TB-vulnerable family groups can be carried out continuously so that TB transmission can be prevented early. Keywords: Tuberculosis, Screening, Education